Regulations on nutrition in Indonesia and its relation to early childhood caries - Amalia, Rosa; Siregar, Fitrina R.; Alfian, M. Fahmi; Arie Sandy, Leny P. (Frontiers in Public Health, 2022)
There is a close relationship between food and nutrition policies and oral health. The relationship between nutrition and dental problems has been widely discussed, including the major dental problem in children: early childhood caries (ECC). Health-oriented national policies are the main principles of public health welfare. This article is a policy brief that provide a review of the food and nutrition policies in Indonesia that may have a relationship with ECC. It is concluded that some policies support the efforts to prevent ECC however, other technical explanations are still needed for health workers and especially parents regarding its simple implementation in everyday life. Multisectoral approaches that includes health, nutrition and education are needed to address ECC.